(untitled) (Research, Society and Development, 2022)
Cow’s milk protein allergy (CMPA) is a growing pathology in early childhood. Anthropometric and nutritional assessment and adherence to diets are essential during the treatment of children with this allergy. The objective of this study was to evaluate the anthropometric and nutritional status of children with CMPA in Teresina-PI. Therefore, a quantitative, transversal, exploratory and descriptive research was carried out, with anthropometric and nutritional data of children of both sexes diagnosed with CMPA, aged up to 6 years. Data were collected through online questionnaires applied to parents or guardians, in the city of Teresina-PI, from September to December 2021. Participants were recruited from the disclosure of research intent on social networks and through the availability of contacts of possible research participants, with maternal and child nutritionists. With this research, it was found that the majority of children with CMPA studied were in adequate nutritional status and with good adherence to the proposed treatment, results observed both during treatment and in the current period of the study, after treatment. In view of this, it can be observed that hypersensitivity to cow’s milk protein did not directly affect the nutritional status of the children studied, which may be associated with adequate professional monitoring and good adherence to the diet during treatment.